Estudio queiloscópico en estudiantes de la Facultad de Odontología de la Universidad de Antioquia - Molano-O., Mauricio Andrés; Gil-C., Jorge Humberto; Jaramillo-R., Johana Andrea; Ruiz-G., Sandra Maritza (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The objective of this study was to let the professional dentist and the dental student know about a scientific method of personal identification that is being formulated, that is easy to carry out, and that besides the dental records, can be easily implemented in professional practice due to its low cost and to the fact that it doesn't require a great amount of time and knowledge. It will eventually allow the dentist to keep a file of prints and lip forms that will support the forensic work, further research, or simply when the justice requires it. The sample consisted of 168 dental students from the College of Dentistry of the University of Antioquia, a photograph of the lips was taken to each one of the students, in them, commisural shape and lip thickness were identified, then, a piece of tape was placed across the lips in such a way that it would reveal the labial print in order to make the analysis easier. It was found that the type III print (Suzuky-Tsuchihashi), is the most common one among the population studied, this finding coincides with the results observed in previous studies done in subjects of a race different than the South American crossbred. It was also concluded that the cheiloscopic study is a tool of easy access to any dentist, and can be implemented as an auxiliary method of identification. Key words: cheiloscopics, print, lips, identification.